CAPACITY BUILDING DPMD BOJONEGORO DALAM PEMBINAAN PEMERINTAHAN DESA UNTUK PENCEGAHAN KORUPSI - Musta’ana; Livia Abtarian; Faridatul Istighfaroh (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2026)
This examination analyzes the implementation of capacity-building by the Bojonegoro Regency Community and Village Empowerment Agency (DPMD) to promote village governance and prevent corruption amid rampant mismanagement of Village Funds. A qualitative case study approach based on Grindle's (1997) theory was used, through in-depth interviews with eight key informants, field observations, and document analysis. The conclusions indicate that the DPMD has conducted SISKEUDES-CMS training, provided technical guidance on goods/services procurement, and facilitated multi-stakeholder collaboration involving the Prosecutor's Office, the Police, and the Village Consultative Body (BPD), thereby increasing village financial transparency and accountability by 89%. Nonetheless, implementation remains partial due to limited digital human resources in remote villages and minimal systemic policy integration. This study recommends institutional reform through steady monitoring and community participation to ensure integrity in village governance